2020
DOI: 10.1093/jas/skaa278.355
|View full text |Cite
|
Sign up to set email alerts
|

268 Administering an appeasing substance to optimize welfare and performance of receiving cattle

Abstract: This experiment evaluated the impacts of bovine appeasing substance (BAS) administration on performance, health, and physiological responses of feedlot cattle during a 45-d receiving period. A total of 342 recently-weaned Angus-influenced steers, originating from 16 cow-calf operations, were obtained from an auction yard on d -1 and road-transported (12 h) to the feedlot. Upon arrival on d 0, body weight (BW) was recorded and steers were ranked by BW and source and assigned to receive BAS (Nutricorp, Araras, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 0 publications
4
7
0
Order By: Relevance
“…Indeed, in their study, incidence of BRD was greater (p < 0.05) in Angus steers that received appeasing pheromone than in the control group during Days 6-10 and 19-23, although overall BRD incidence did not differ between treatments. Moreover, a higher proportion (p = 0.04) of the appeasing pheromone group diagnosed with BRD required one antimicrobial treatment to retrieve health compared to control group [26]. Similarly, in our study, we detected more clinical signs in the pheromone group than in the control group early, on D8.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…Indeed, in their study, incidence of BRD was greater (p < 0.05) in Angus steers that received appeasing pheromone than in the control group during Days 6-10 and 19-23, although overall BRD incidence did not differ between treatments. Moreover, a higher proportion (p = 0.04) of the appeasing pheromone group diagnosed with BRD required one antimicrobial treatment to retrieve health compared to control group [26]. Similarly, in our study, we detected more clinical signs in the pheromone group than in the control group early, on D8.…”
Section: Discussionsupporting
confidence: 78%
“…Among the potential alternatives, bovine appeasing pheromone is an attractive one. As stated above, several previous reports have shown a benefit when appeasing pheromones were used in dairy and beef cattle production [22,[24][25][26]. In our study, carried out in fattening units from western France using Charolais young bulls, we observed that significantly more clinical cases were detected on day 30 (D30) in the control group than in the group of bulls which received appeasing pheromone, while the opposite was observed earlier on D8.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations